2011
DOI: 10.1038/nature09797
|View full text |Cite
|
Sign up to set email alerts
|

Habenular α5 nicotinic receptor subunit signalling controls nicotine intake

Abstract: Genetic variation in CHRNA5, the gene encoding the α5 nicotinic acetylcholine receptor (nAChR) subunit, increases vulnerability to tobacco addiction and lung cancer, but underlying mechanisms are unknown. Here, we report dramatically increased nicotine consumption in mice with null mutation in Chrna5. This effect was `rescued' in knockout mice by re-expressing α5 subunits in medial habenula (MHb), and recapitulated in rats through α5 subunit knockdown in MHb. Remarkably, α5 subunit knockdown in MHb did not alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
722
5
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(783 citation statements)
references
References 57 publications
51
722
5
5
Order By: Relevance
“…12,13 Unlike the wide distribution of α4β2 nAChR in the brain, the α3 and β4 subunits are expressed in a restricted number of brain areas, mainly the medial habenula and interpeduncular nucleus, major cholinergic tracts in the brain that have recently garnered increasing attention for their involvement in various aspects of nicotine dependence. [14][15][16][17] Consistent with the genetic and knockout studies, a transgenic mouse model overexpressing the human CHRNA5/Α3/Β4 genomic cluster showed significantly increased β4* nAChR binding in the medial habenula and increased acquisition of nicotine self-administration. 18 We recently reported that a potent and selective α3β4 nAChR ligand AT-1001, significantly blocks nicotine self-administration in rats, at relatively low doses (0.75-3 mg/kg) given subcutaneously, without affecting nonspecific food responding.…”
Section: Introductionsupporting
confidence: 48%
“…12,13 Unlike the wide distribution of α4β2 nAChR in the brain, the α3 and β4 subunits are expressed in a restricted number of brain areas, mainly the medial habenula and interpeduncular nucleus, major cholinergic tracts in the brain that have recently garnered increasing attention for their involvement in various aspects of nicotine dependence. [14][15][16][17] Consistent with the genetic and knockout studies, a transgenic mouse model overexpressing the human CHRNA5/Α3/Β4 genomic cluster showed significantly increased β4* nAChR binding in the medial habenula and increased acquisition of nicotine self-administration. 18 We recently reported that a potent and selective α3β4 nAChR ligand AT-1001, significantly blocks nicotine self-administration in rats, at relatively low doses (0.75-3 mg/kg) given subcutaneously, without affecting nonspecific food responding.…”
Section: Introductionsupporting
confidence: 48%
“…Work from Fowler and Kenny demonstrated that α5-KO (α5-expressing nAChRs are enriched in the vMHb-IPN pathway) mice show escalations of nicotine self-administration through a blunting of the aversive properties of nicotine and not an increase in the rewarding aspects of the drug (Fowler & Lu Qun 2011;Tuesta et al 2011). Conversely, pharmacological antagonism of β4-expressing nAChR (also enriched in the vMHb-IPN pathway) inhibits the self-administration of morphine and cocaine and blocks the formation of cocaine CPP (Glick et al 2006;McCallum & Glick 2009;Khroyan et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the density of cholinergic neurons and the expression of unique nicotinic acetylcholine receptors (including the β4 and α5 subunits) in the vMHb, much of the addiction field has focused on nicotine-associated behaviors (Salas et al 2009;Fowler, Lu Qun 2011;Fowler & Kenny 2012;Velasquez et al 2014;Tuesta et al 2017). The cholinergic population of the vMHb has been shown to be necessary for nicotine selfadministration, withdrawal and the aversive properties of nicotine (Fowler & Lu Qun 2011;Frahm et al 2011;Antolin-Fontes et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of association with the CHRNA6-CHRNB3 locus may merely reflect its weaker association with nicotine dependence, consistent with its relatively modest association in GWAS of cigarettes per day in other studies. However, it is also possible that these genetic loci influence smoking behaviors via separate mechanisms that differentially impact levels of CO versus number of cigarettes smoked per day (e.g., influencing responses to nicotine in the initiation of smoking behaviors versus promoting more intense smoking of individual cigarettes and increased tolerance to smoking's aversive effects) (41,42). The existence of separable mechanisms influencing levels of CO versus amount smoked is consistent with findings that the CHRNA6-CHRNB3 locus shows little contribution to the genetic risk of COPD and lung cancer in the large-scale studies (43,44).…”
Section: Original Researchmentioning
confidence: 99%